Impact of Nordic walking on health outcomes in older women - E. V. Katamanova; I. V. Kudaeva; L. S. Vasilyeva; A. N. Kudaev; N. V. Verlan (National Electronic Information Consortium (NEICON), 2023)
There are a number of factors that contribute to the accelerated rate of aging, one of which is physical activity. The increasing proportion of elderly and senile people in the Russian Federation requires urgent implementation of the elderly generation subprogram within the framework of the Demography federal project. In this regard, the problems of maintaining health and the development of methodological approaches to assessing the health of people in the older age group are especially significant.Objective: evaluation of anthropometry, stabilometry and biochemical parameters in the dynamics of Nordic walking in elderly womenMaterials and methods: 30 women were examined, mean age 69.0 (63.0-71.5) years. Examination by a therapist and a neurologist, biochemical blood tests, stabilometry, anthropometry, osteodensitometry (ODM) were carried out. Training loads of Nordic walking (NW) for 3 months were carried out according to the generally accepted method 3 times a week.Results: According to the biochemical analysis of blood, a statistically significant increase in the level of phosphorus and alkaline phosphatase (AP), total protein, as well as a decrease in the level of calcium and total cholesterol were revealed. When considering anthropometry data, there was a statistically significant decrease in body weight, BMI, body fat mass according to the Durnin - Womersley method, SBP and an increase in the cardiovascular index. According to the results of computer stabilometry - a statistically significant increase in the average position of the CP in the sagittal plane with open and closed eyes.Conclusion: 1. The use of NW as a training factor to achieve active longevity in the elderly leads to an improvement in the functioning of the cardiovascular system, due to a statistically significant decrease in body weight, a decrease in SBP by an average of 15 mm Hg. art., as well as the level of total cholesterol. 2. With regular NW exercises for 3 months, the functional stability indicators in the sagittal plane are corrected both with open and closed eyes.